Nutrientes y clorofila-a durante el período de inundación 2001-2002 en la Laguna Chascomús (Argentina) - Bustingorry, José Fernando (2008)
Total phosphorus, total nitrogen and chlorophyll-a concentrations were determined weekly in a pelagic zone in Chascomús Pond between April 2001 and September 2002. Two flood periods took part with 8 metres over sea level (IGM) during this time (June- January 2002 and April-June 2002), where in both of them two maximum peaks with about 9 meters were registered. As a consequence a diminution of the salinity to one third of the mean value of 1,57 g.l-1 was observed, because of the dilution promoted by rainwater which was higher in a 40% of the mean 600 mm of the latest five years. Nevertheless, this fact had not occurred with total phosphorus, mean 0,48 mg.l-1, referring to 0,48 mg.l-1 obtained in 1999-2000, while total nitrogen, mean 1,45 mg N.l-1, was nearly in the same order in relation to a previous value of 1,56 mg N.l-1 (1983-1984) and chlorophyll-a, mean 198,2 μg.l-1, showed a significant increment taking into account the concentration of 89,1 μg.l-1 determined during 1999-2002. These results indicate that because of flood events a supply of nutrients reaches the pond coming from wastes of the city (30000 inhabitants), as well as from the effluent of the treatment plant. Normally, the latter go to Girado stream and finally are received by Adela Pond in direction to Salado River, but the inversion of the flux makes these wastes reach Chascomús Pond during flood periods.